Bosonic Coherent Motions in the Universe - Jihn E. Kim; Yannis Kyriakos Semertzidis; Yannis Kyriakos Semertzidis; Shinji eTsujikawa (Frontiers in Physics, 2014)
We review the role of fundamental spin-0 bosons as bosonic coherent motion (BCM) in the Universe. The fundamental spin-0 bosons have the potential to account for the baryon number generation, cold dark matter (CDM) via BCM, inflation, and dark energy. Among these, we pay particular attention to the CDM possibility because it can be experimentally tested with the current experimental techniques. We also comment on the panoply of the other roles of spin-0 bosons--such as those for cosmic accelerations at early and late times.